Budzhak Topos in the Ukrainian Danube Region Poetry: Array - Raibedyuk, Halyna (Journal of Danubian Studies and Research, 2020)
The article deals with the creative works of modern Russian-speaking poets of Budzhak (Oksana Kartelyan, Sergei Levin, Marina Kopanoy, Lyudmila Oleynik, Nadezhda Parshikhina, Yuri Yakimenko and others). In their lyrics the peculiarities of verbal integration of the key markers of the geographical component in the authors' world pictures are revealed. The main attention is focused on the characteristics of individual modes of the Budzhak topos representation in the creative practice of this circle of poets. The vision of the regional space in their poems is presented through a system of images and motifs associated with the Danube toponyms as markers of a particular territory and as original artistic structures. It is noted that among the most frequent toponyms the artistic world of Russian-speaking poets of Budzhak was formed by two of their varieties: oikonyms (Izmail, Kiliya, Bolgrad) and hydronyms (Danube river, Yalpug lake). The ideological and aesthetic role of poetonyms in the author's text and in the general context of the regional literature of the Danube region is traced and characterized.